2006
DOI: 10.1177/1362361306068510
|View full text |Cite
|
Sign up to set email alerts
|

Living with ASD

Abstract: Social interaction and understanding in autistic spectrum disorder (ASD) are key areas of concern to practitioners and researchers alike. However, there is a relative lack of information about the skills and competencies of children and young people with ASD who access ordinary community facilities including mainstream education. In particular, contributions by parents and their children have been under-utilized. Using two structured questionnaires, 19 children with ASD reported difficulties with social skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…Similarly, Koning and Magill-Evans (2001) observed that, although a group of adolescent boys with ASP had some awareness of their social skills deficits, they assessed themselves as having more social skills than their parents and teachers reported them to possess. Knott et al (2006) described similar findings; self-reports by children and adolescents with ASD indicated greater levels of social skills and social competence relative to parent-reports.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, Koning and Magill-Evans (2001) observed that, although a group of adolescent boys with ASP had some awareness of their social skills deficits, they assessed themselves as having more social skills than their parents and teachers reported them to possess. Knott et al (2006) described similar findings; self-reports by children and adolescents with ASD indicated greater levels of social skills and social competence relative to parent-reports.…”
Section: Introductionsupporting
confidence: 79%
“…As such, the parents of our ASD sample may have assigned higher ratings to some of the ASD associated traits exhibited by their children than parents of control participants assessing the same behaviours. However, in light of previous findings (Green et al 2000;Knott et al 2006;Koning and Magill-Evans 2001), the discrepancy observed between self-and parent-reports identified in this current study likely reflects poorer selfperception to a greater extent than over-reporting by parents. Furthermore, it is important to keep in mind that parents and youths did not differ on the SQ.…”
Section: Understanding Discrepancies Between Raterscontrasting
confidence: 70%
See 1 more Smart Citation
“…It could also be that children with ASD are encouraged to talk about their thoughts and feelings, particularly those dealing with anxiety and upset, as those are a major issue for them and may be explicitly confronted with parents, teachers, and therapists, promoting higher agreement. Consistent with this, studies examining whether ASD individuals have insight into their specific psychiatric symptoms – termed “clinical insight” (Beck et al, 2004) – as well as life difficulties stemming from them, such as academic and physical problems, suggest moderately high self-other agreement (median r = .45), although with a very broad range of results across studies (range = −.08 to .73) (Farrugia & Hudson, 2006; Johnson et al, 2009; Knott et al, 2006; Koning et al, 2001; Vickerstaff et al, 2007). …”
Section: Discussionmentioning
confidence: 80%
“…However, the findings suggest that the training is still generalizable to adults with ASD as they demonstrated significantly improved job interview skills between the baseline and follow-up role-play sessions as well as increased self-confidence. Although a greater increase in self-confidence in the intervention group was observed, this finding should be interpreted with caution as individuals with ASD have difficulty with self-report and may overestimate their abilities (Knott et al 2006). Moreover, unexpected interview responses may potentially be more common among individuals with ASD and present possible limitations to the use of VR-JIT, which uses scripted responses.…”
Section: Discussionmentioning
confidence: 80%